2010
DOI: 10.1111/j.1600-0501.2009.01855.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of autologous venous blood for maxillary sinus floor augmentation in conjunction with sinus membrane elevation: an experimental study

Abstract: The results of this pilot study indicate that blood clots do not have sufficient integrity to enable the sinus membrane to remain in an elevated position for therapeutically effective periods of time. Accordingly, it is recommended that this method be used only when a small amount of new bone formation is necessary around implants in the maxillary sinus cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 15 publications
1
50
1
3
Order By: Relevance
“…To enhance bone formation in the maxillary sinus floor using sinus membrane elevation, graft materials or techniques that enable the membrane to remain in the elevated position are necessary [7] . The results of Kim et al (2010) [8] study were different from the findings of Hatano et al (2007) [6] , who stated that the mean bone height gained was 10mm 6 months following the procedure. The inconsistency of these results may have resulted from the use of different methods of evaluating endosinus bone gain.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…To enhance bone formation in the maxillary sinus floor using sinus membrane elevation, graft materials or techniques that enable the membrane to remain in the elevated position are necessary [7] . The results of Kim et al (2010) [8] study were different from the findings of Hatano et al (2007) [6] , who stated that the mean bone height gained was 10mm 6 months following the procedure. The inconsistency of these results may have resulted from the use of different methods of evaluating endosinus bone gain.…”
Section: Discussioncontrasting
confidence: 54%
“…The increased thrombin generation on the surfaces of titanium implants may also stimulate proliferation and inhibit apoptosis of osteoblasts [11] . Using a patient's own venous blood to treat posterior maxillary atrophy has various theoretical advantages, including ease of procurement and application, lack of adjunctive grafting materials, and the presence of growth factors in blood platelets [8] . According to the previous study about this technique, Lundgren et al demonstrated that wherein the maxillary sinus membrane was elevated and bone was spontaneously formed in the blood clot around implants which had been placed in the residual alveolar bone [17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors other than the implant surface could have affected the amount of bone gain, such as the buccopalatal width of the sinus. 19,20 In addition, a major shortcoming of this study was the nonrandomized allocation of the 2 types of implants used. To evaluate the relevance of the implant surface or other factors to bone generation at the buccal and palatal sites of the implant in detail, further studies with randomized allocation are needed.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] This finding supports the fact that bone formation with the sinus infiltration technique depends on the swelling in the space created by the membrane elevation rather than the volume of bone grafting material added in the procedure. 25,26 In conclusion, this radiographic analysis showed new bone formation surrounding implants following augmentation of the maxillary sinus floor with the sinus infiltration technique. The manner of bone formation with this technique appears to be different from that occurring with the conventional lateral sinus floor elevation.…”
Section: Discussionmentioning
confidence: 93%